UJI DAYA HAMBAT EKSTRAK DAUN BUNGA TANJUNG (Mimusops elengi L.) TERHADAP PERTUMBUHAN Candida albicans - Antika, Wella; Indriati, Gustina; Irdawati, Irdawati (STKIP PGRI Sumbar, 2014)
ABSTRACT Petal cape ( Mimusops elengi L.) is one of the medicinal plants . Petal cape contains chemical compounds that act as anti- microbial . These chemical compounds are saponins , alkaloids and tannins , but it is not certain the extent of inhibition of petal cape on the growth of Candida albicans . Based on the research that has been done Inhibition Test Leaf Extract Flower Power Cape ( M. elengi L.) on growth of C. albicans . This research used Completely Randomized Design ( CRD ) with 7 treatments and 3 replications starting from Albothyl control( A ) 2 % , cape flower leaf extract ( B ) 5 % , ( C ) 10 % , ( D ) 20 % , ( E ) 30 % , ( F ) 40 % , ( G) 50 % . Data were analyted using Analysis Of Variance ( ANNOVA ) . Study aimed to determine the inhibition of leaf extracts of flowers cape ( M. Elengi L. ) on the growth of C. albicans , and to determine the most effective concentration of leaf extracts of flowers cape ( M. elengi L.) to the growth ( C. albicans ) performed in microbiology laboratories UNP . The results showed that the leaf extract of flower cape ( M. elengi L.) were able to inhibit the growth of Candida albicans . And found that the most effective concentration in treatment C ( 10 % ) is equal to 1.74 mm , and the concentration of the smallest on the control that is equal to 1.34 mm . From the research that has been carried out it was concluded that the extract from the leaves of flowers tanjung with a concentration of 5 % to 50 % can inhibit the growth of C. albicans , meaning headland petals can be used as an alternative to treat canker sores in the mouth .